Agromorphological and Physicochemical Characteristics of Golden Rice , Introduced Rice Line PAC Nagdong/IR36/IR64 - Danny Agus Dyansyah; Evita Nuril Aisiyah; Elvina Azaria Fatimah; Angger Aisyah Hadiahning Gusti; Mohammad Ubaidillah (Institut Pertanian Bogor, 2026)
Golden Rice (Oryza sativa L.) is biofortified rice that contains β-carotene, an essential nutrient for human health. Golden Rice PAC Nagdong/IR36/IR64 was created by crossing PAC Nagdong/IR36 with IR64 rice, a native variety, to improve tolerance to Indonesia's environment. Observations were made in two stages: (a) agromorphological characterization during culture, which included plant height, tiller number, panicle length, fertility, yield potential, and grain color, and (b) physicochemical analysis to assess amylose, amylopectin, protein, and lipid levels. Golden Rice has semi-dwarf height, a good and very high number of tillers (22.60−24.40), a panicle length of 20.09−20.85 cm, grain weight per pot of 42.08−42.94 g, fertility of 67.23−81.54%, and seed color of 5Y 8/8−5Y 8/10. The physicochemical properties included amylose content of 12.41−13.37%, protein content of 4.61−5.45%, lipid content of 1.24−1.54%, swelling power of 6.72−8.08%, low gelatinization temperature, and soft gel consistency type. The results indicated Golden Rice line 302/IR-2-2(7)/2 exhibit superior characteristics, including lower amylose and protein contents, higher fertility, and soft gel consistency which identical with consumer-preferred rice quality in Indonesia. Accordingly, this line have the highest potential for commercialization, while the remaining lines depict as promising materials for further breeding improvement. Keywords: agromorphology, Golden Rice , physicochemistry